Subconjunto terminológico da Classificação Internacional para a Prática de Enfermagem (CIPE® ) para o cuidado à gestante durante o trabalho de parto - Alencar, Cleyse Caroline Alves de (2023)
The use of the nursing process contributes to the continuity of care and comprehensive care. Taking into account the reduced number of nursing diagnostic concepts specifically aimed at care during labor, in addition to the lack of a terminological subset of the International Classification for Nursing Practice (ICNP® ) on the subject and the importance of the nursing process, nursing and the systematization of care, this dissertation aimed to develop a terminological subset of the ICNP® for the care of pregnant women during labor. The research was carried out through a methodological study consisting of four stages and with the participation of specialist professionals who work in the care of pregnant women during labor, to evaluate and validate the terms found. The steps were: 1) identification of relevant terms; 2) cross-mapping of identified terms with ICNP® terms; 3) selection of precoordinated Diagnosis (ND), Results (NR) and Nursing Interventions (NI) statements; 4) structuring of the terminological subset. In the first stage, relevant terms about the theme were collected through integrative review and analysis with the IRaMuTeQ software, which underwent a validation process to certify their relevance for clinical practice; in the second, a cross-mapping of the validated terms with the terms contained in the ICNP® was carried out; in the third stage, the statements ND/NR and NI were selected; and, in the last stage, the terminological subset was built with the statements, subdivided according to Horta's Theory of Basic Human Needs. The integrative review resulted in 19 articles for analysis. After the exhaustive and complete reading of the 19 articles, and the analysis of the IRaMuTeQ software, 39 terms were found to compose the validation instrument. Cronbach's alpha reliability test was performed to assess the reliability level of the research instrument, totaling an alpha value of 0.957, resulting in an internal consistency considered excellent. Validation was carried out by 20 expert evaluators in the area and, after evaluating the instrument, 24 terms were validated. After crossing validated terms and precoordinated ICNP® concepts, 15 terms were associated with diagnostic statements, resulting in 21 Nursing Diagnosis statements and 167 Nursing Interventions associated with these ND, thus composing the Terminological Subset, divided according to Basic Human Needs and their domains, from Wanda Horta's Theory. The elaboration of the ICNP® Terminology Subset for the care of pregnant women during labor aims to contribute to nursing care through the construction and availability of a tool with standardized and unified language in order to support nursing practice based on evidence and favor the implementation of the nursing process, directing the actions of professionals in the area.